Pengalaman Hidup Anak Jalanan Usia Remaja - Chatarina Suryaningsih; Muhammad Fadli Nur (Jurnal Keperawatan Silampari, 2020)
The purpose of this study is to describe the life experiences of street children in adolescence. This research method is qualitative research using a descriptive phenomenology approach to tell street children aged adolescents' life experiences. This study resulted in 4 research themes, namely factors causing street children, family and community responses to street children, life descriptions of being street children, and the aspirations of street children. In conclusion, the life experiences of street children produce four major themes according to the research results. Keywords: Street Children, Qualitative, Life Experience, Adolescents